2021
DOI: 10.1002/hep.32115
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association of individual vulnerability with alcohol‐associated liver disease: A Korean genome and epidemiology study

Abstract: This study was conducted with bioresources provided by the National Biobank of Korea, the Centers for Disease Control and Prevention, Republic of Korea (2019-059). The work was funded by the Ministry of Trade, Industry and Energy of Korea (20002781).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Another recent study found three loci, ZNF827, GGT1, and HNF1A, to be significantly associated with ALD risk [144]. Other GWASs for ALD revealed candidate genes such as GABRB1, DRD4 and TH, PECR, PDLIM5, METAP, ADH1C, etc.…”
Section: Gwas Loci For Predisposition and Susceptibility Of Aldmentioning
confidence: 98%
“…Another recent study found three loci, ZNF827, GGT1, and HNF1A, to be significantly associated with ALD risk [144]. Other GWASs for ALD revealed candidate genes such as GABRB1, DRD4 and TH, PECR, PDLIM5, METAP, ADH1C, etc.…”
Section: Gwas Loci For Predisposition and Susceptibility Of Aldmentioning
confidence: 98%
“…Of note, this mechanism drives the full spectrum of fatty liver diseases, ranging from fatty liver to steatohepatitis, progressive fibrosis, cirrhosis, and HCC. [5] In this issue of Hepatology, Kim et al [6] used the KoGES (Korean Genome and Epidemiology Study) Health Examination cohort, comprising 40-to 79-year-old Korean persons from an urban area who were recruited from a national health examinee registry and genotyped by the National Biobank of Korea. [7] Based on questionnaires of 21,919 participants, they identified 782 (4.1%), 1,379 (9.5%), and 1,185 (34.5%) patients who presented with gamma-glutamyl transferase (GGT)/alanine aminotransferase >2.5 or aspartate aminotransferase/ALT > 3.0 (used as indicators of AALD) without an overt drinking history or with a history of consuming less or more than 140 g (women) and 210 g (men) of alcohol per week, respectively.…”
Section: Vulnerability To Alcohol-associated Liver Disease: a Tale Of...mentioning
confidence: 99%
“…The study by Kim et al [ 6 ] highlights that genetic susceptibility to AALD is multifactorial and suggests that genetic vulnerability is modulated by the quantity of alcohol consumed. The observations are consistent with meta‐analyses [ 8 ] reporting that alcohol consumption amplifies the genetic risk driven by PNPLA3.…”
mentioning
confidence: 99%
“…A GWAS was carried out in the Korean Genome and Epidemiology Study Health Examination cohort data to assess the risk of developing ALD in nondrinkers, light drinkers, and heavy drinkers. The study r e p o r te d a n a s s o c i a t i o n of lo c i , n a m e l y ga m m aglutamyltransferase 1 (GGT1; rs2006227), zinc protein finger 827 (ZNF827; rs1183910), and HNF1 homeobox A (HNF1A; rs1183910) with ALD risk, in addition to 5 variants on Chromosome 11 that showed protective effects against ALD (35).…”
Section: Patatin-like Phospholipase Domaincontaining Proteinmentioning
confidence: 99%